GEOLOGY AND ORE MINERALISATION OF NEOGENE SEDIMENTARY ROCK HOSTED LS EPITHERMAL GOLD DEPOSIT AT PANINGKABAN, BANYUMAS REGENCY, CENTRAL JAVA, INDONESIA - Arifudin Idrus; Fahmi Hakim; I Wayan Warmada; Mochammad Aziz; Jochen Kolb; Franz Michael Meyer (Geological Engineering Department Universitas Gadjah Mada, 2015)
Low suphidation (LS) epithermal gold deposits were recently found in the Paningkaban area, Central Java province, Indonesia, with more than ﬁve hundred artisanal gold miners currently operating in the area. This study is aimed to understand the geological factors controlling the gold mineralization and to characterize the alteration and ore mineralogy of the deposit. Several epithermal veins/veinlets trending N–S, NW–SE, and NE–SW are hosted by Tertiary turbiditic volcanoclastic sedimentary rocks of the Halang formation. This formation is composed of looping gradation of sandstone and siltstone units. Pre- and syn-mineralization structures such as extension joints, normal sinitral fault and sinitral fault control the gold mineralization. Fault movements formed dilational jogs manifested by NW-SE-trending en-echelon tension gash veins. Four main alteration zones are identiﬁed: (a) phyllic, (b) argillic, (c) sub propylitic and (d) weak subpropylitic. Ore minerals consist of native gold, electrum, native silver, pyrite, chalcopyrite, sphalerite, galena, arsenopyrite, cubanite, marcasite, covellite and tennantite, which are commonly associated withargillic alteration. Vein structures such as massive, swarm and low angle veins, stockwork and veins dispersed in diatreme breccia are present. Normal banded, cockade, crustiform, bladed carbonates as well as, comb and saccharoidal features are the typical vein textures. It is noteworthy that the veins are basically composed of carbonate with minor quartz at gold grades of up to 83 g/t Au. Based on the vein structures and textures, four stages of ore mineralization were developed consisting of (a) early stage (ﬂuidized breccia and quartz vein), (b) middle stage (carbonate base metal), (c) late stage (late carbonate), and supergene stage. Gold mineralization originated mainly during middle and late stages, particularly in association with cockade, crustiform, bladed carbonate base metal veins. Based on those various features, the LS epithermal deposit in the study area is categorized as carbonate-base metalgold mineralization type.